Optimal dose and type of exercise improve walking velocity in adults with Parkinson’s disease: a systematic review and Bayesian network meta-analysis - Shaoqing Xie; Yuan Yuan; Junyu Wang; Ying Bai; Tao Wang; Bopeng Qiu; Yong Yang; Shu-Cheng Lin (Scientific Reports)
Abstract To examine the dose–response relationship between specific types of exercise for improving walking velocity in Parkinson’s disease (PD). This systematic review and network meta-analysis included searches of PubMed, Medline, Embase, PsycINFO, Cochrane Library, and Web of Science were searched from inception until February 18th, 2024. Data analysis was performed using R software with the MBNMA and RJAGS packages. Outcome indicators were measured as mean standard deviation (SMD) along with 95% confidence intervals (95% CrI). The network’s risk of bias was independently evaluated by two reviewers employing the ROB2 tool. Our review encompassed 54 studies with 2,828 PD patients, examining the dose–response effects of different exercises on walking velocity. Aerobic Exercise (AE) demonstrated the greatest improvement at an optimal dose of 1,400 METs-min/week (SMD:1.215, 95% Crl: 0.113 to 2.306). Both Multicomponent Exercise (Mul) (SMD: 1.202, 95% Crl: 0.193 to 2.231) and Sensory Exercise (SE) (SMD: 0.649, 95% Crl: 0.139 to 1.183) showed optimal outcomes at a dose of 1,000 METs-min/week. Resistance Training (RT) was most effective at 750 METs-min/week (SMD:0.778, 95% Crl: 0.062 to 1.549), while Mind–Body Exercise (MBE) yielded significant improvements at a lower optimal dose of 500 METs-min/week (SMD: 0.580, 95% Crl: 0.218 to 1.137), offering valuable insights for exercise prescription in PD management. Various types of exercise showed specific optimal benefits at corresponding doses, among which AE was the most effective in improving the walking speed of PD patients at 1,400 Mets*min/week. Trial registration: PROSPERO (CRD42024506919).